PENGARUH PBB, PAJAK RESTORAN DAN PAJAK HIBURAN TERHADAP PAD KOTA KEDIRI TAHUN 2018-2022 - Susanti, Agustiana Ayu; Nurdiwaty, Diah; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this research are: (1) to determine the effect of Property Tax (PBB) on Local Revenue (PAD) of Kediri City from 2018 to 2022, (2) to determine the effect of restaurant tax on Local Revenue (PAD) of Kediri City from 2018 to 2022, (3) to determine the effect of entertainment tax on Local Revenue (PAD) of Kediri City from 2018 to 2022, (4) to determine the effect of Property Tax (PBB), restaurant tax, and entertainment tax on Local Revenue (PAD) of Kediri City from 2018 to 2022. This research employs a quantitative causal approach using secondary data sources. The data collection technique used in this research is documentation and analysis using multiple linear regression analysis. The results of this research conclude that Property Tax (PBB) does not have a significant effect on Local Revenue (PAD), while restaurant tax and entertainment tax have a significant partial effect on Local Revenue (PAD), and simultaneously, Property Tax (PBB), restaurant tax, and entertainment tax have a significant effect on Local Revenue (PAD). In this study, an additional independent variable was introduced, which is Property Tax (PBB), whereas the previous study conducted by Permadi & Salam (2022) only involved local taxes in the tourism sector. Furthermore, the technique of normality testing in this research used the Jarque-Bera statistical analysis method, with the intention of demonstrating any differences compared to the commonly used techniques in previous research.